Autoantibodies in type 1 diabetes: Prevalence and clinical profiles - Raja Hazime; Saad Lamjadli; Morad Guennouni; Mounir Belkrachni; Fatima-Ezzohra Eddehbi; Ider Oujamaa; Lahcen Elmoumou; Aicha Bourrahouate; Imane Ait Sab; Hicham Baizri; Nawal El Ansari; Brahim Admou (Diabetes Epidemiology and Management)
Type 1 diabetes mellitus (T1D) is one of the most common chronic diseases in children and is associated with acute and serious chronic complications. T1D is characterized by the destruction of insulin-producing beta cells in the pancreas, with the emergence of circulating autoantibodies (a-Abs) targeting β cell antigens. Identifying autoantibodies can help predict the onset of T1D and associated autoimmune disorders, enhancing patient management strategies.We aimed to determine the prevalence of T1D autoantibodies and their clinical significance in the pediatric and adult populations. A multicenter cross-sectional study was carried out on 276 patient-first with T1D, including 167 pediatric (60.5 %) and 109 adult (39.5 %) cases, of which 144 were female and 132 were male (sex ratio= 0.91),with an average age of 14.1 ± 8.0 years. The immunological investigation was based on the detection of T1D related a-Abs, including anti-insulin, anti-glutamic acid decarboxylase (GAD65), anti-insulinoma-associated antigen 2 (IA2), and anti-zinc transporter 8 (ZnT8) specificities. The results revealed an overall autoantibody seropositivity rate of 75.36 % (n= 208). Among the positive cases, GAD65 antibodies were the most prevalent at 37.31 %, followed by anti-insulin and anti-ZnT8 antibodies, each at 36.59 %, and anti-IA2 at 28.62 %. Additionally, 45,67 % of patients had one a-Abs, 28.36 % had a two, 21.15 % had three, and 4.8 % had all four a-Abs.A statistically significant difference was observed between the seropositive and seronegative groups regarding the presence of associated autoimmune diseases (p = 0.005). These findings align with the existing literature, highlighting the importance and scientific value of detecting a-Abs in patients with T1D.